Galanin analogs prevent mortality from seizure-induced respiratory arrest in mice - Collard, Ryley; Aziz, Miriam C.; Rapp, Kevin; Cutshall, Connor; Duyvesteyn, Evalien; Metcalf, Cameron S. (Frontiers in Neural Circuits, 2022)
Objective: Sudden Unexpected Death in Epilepsy (SUDEP) accounts for 20% of mortality in those with recurrent seizures. While risk factors, monitoring systems, and standard practices are in place, the pathophysiology of SUDEP is still not well understood. Better knowledge of SUDEP and its potential mechanisms of action is crucial to reducing risk in this patient population and developing potential treatment options. Clinical studies and animal models of SUDEP suggest that diminished post-ictal respiratory control may be the dominant mechanism contributing to mortality. Recently, it was demonstrated that the depletion of the neuropeptide galanin in the amygdala occurs in human SUDEP. The amygdala plays a key role in the central integration of respiratory signaling; the depletion of galanin may represent a critical change that predisposes individuals to SUDEP. Methods: To evaluate the impact of enhancing galaninergic signaling to potentially protect against SUDEP, we studied seizure-induced respiratory arrest (S-IRA) following central (intracerebroventricular, intra-amygdala) and systemic (intraperitoneal, subcutaneous) administration of galanin analogs. Seizure naïve and seizure experienced (fully kindled) mice were tested. Results: Central and systemically-administered galanin analogs protect against S-IRA in naïve C57Bl/6J mice. Differential efficacy between receptor subtype-selective analogs varied based on the route of administration. Sub-chronic systemic administration at doses that reduced 6 Hz seizures also protected against S-IRA. Acute treatment benefits also extended to fully kindled mice experiencing tonic extension. Significance: These data demonstrate that galanin analogs may be protective against post-ictal respiratory collapse.